Meios alternativos de resolução de conflitos urbanos e justiciabilidade do direito fundamental social à moradia - Pereira, Felipe Pires (2011)
The main objective of this dissertation is to demonstrate that the prediction of housing rights in International Human Rights norms and their explicit inclusion on the list of the social rights of the Brazilian Federal Constitution imposes on states and individuals the obligation to protect and promote this right to socially and economically vulnerable citizens. This theoretical research finds strength in fundamental constitutional principles of urban policy and understanding of the right to housing as a fundamental social right rooted in the principles of human dignity, citizenship, equality, non-discrimination, solidarity, and the review of legal institutions and property ownership in the light of social function. The new approach to access to Justice is the instrumental bond for claiming the right to housing before Government, especially through the exercise of the powers conferred to the Public Defender by the constitutional legislator. The proposed results are the implementation of the fundamental social right to housing through a rights education, mediation and international mechanisms of protection, as well as the bringing of legal individual and collective actions for social protection of this right in a defensive and comprehensive perspective of fundamental rights